China's capitalism a paradoxical route to economic prosperity - Ten Brink, Tobias 1976- (University of Pennsylvania Press, 2019)
In China's Capitalism, Tobias ten Brink reveals how combinations of three heterogeneous actors--party-state institutions, firms, and workers--led to China's distinctive form of capitalism. Presenting a historically nuanced portrait, the book is essential reading for anyone interested in China's socioeconomic order and its future development
Originally published in German in 2013
Keywords: Wirtschaftsentwicklung; Wirtschaftswachstum; Sozialistische Marktwirtschaft; Politische Ökonomie; Kapitalismus; China; Hochschulschrift